Gagasan Al-Qur'an tentang Hukum Sejarah - Hasbi, Artani (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
The Qur'an speaks of human beings as closely associated with the laws of history. Many verses contain a suggestion to human about the role of history. Humans have to adjust the provisions that have been established on the facts and reality that clear and complete. Conditions set by God is a